2002
DOI: 10.1192/bjp.180.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Health of the Nation Outcome Scales for People with Learning Disabilities (HoNOS–LD)

Abstract: HoNOS-LD is an appropriate instrument for measuring outcome in people with learning disabilities with additional mental health needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 13 publications
0
77
0
Order By: Relevance
“…) and global functioning as measured by the HoNOS‐LD (Roy et al . ). They did not find significant improvements in coping skills as measured by the VABS‐II (Sparrow et al .…”
Section: Resultsmentioning
confidence: 97%
“…) and global functioning as measured by the HoNOS‐LD (Roy et al . ). They did not find significant improvements in coping skills as measured by the VABS‐II (Sparrow et al .…”
Section: Resultsmentioning
confidence: 97%
“…A second limitation of the study is the small, and the diagnosis-related sample. The majority of the diagnoses were learning disability where the broad nature of HoNOSCA items may be less well suited to detecting slight changes in such patients (e.g., Roy, Matthews, Clifford, Fowler, & Martin, 2002). However, the main aim of this study (as above mentioned) was not to measure the outcomes of the services, but to evaluate the Greek translation of the instrument.…”
Section: Limitations Of the Studymentioning
confidence: 98%
“…We administered the Symptom Checklist-90-Revised (SCL-90-R) (Derogatis, 1994) to the first intake of clients to the skills group, but found that so many adaptations to item wording were needed that its statistical and clinical utility was compromised, so we stopped using it. For the past three years we have administered the Health of the Nation Outcome Scale -Learning Disability version (HoNOS-LD) (Roy et al, 2002) to carers every three months; initial data suggest the HoNOS-LD may lack sensitivity to measure psychological change. There is currently a lack of DBT-focused outcome measures suitable for adults with an ID, so we have developed and administered our own 18 item psychometric measure (the DBT Carers' Feedback Questionnaire (DBTCFQ)).…”
Section: Evaluation Of Our Dbt Servicementioning
confidence: 99%